Analisis Isi Modul Pengajaran Membaca Berbasis Literasi Kritis Bagi Mahasiswa Calon Guru - Ikaningrum, Rini Estiyowati; Indriani , Lilia (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2023)
The aim of this article is to analyze the content of teaching reading module for student teachers, so they have ability to proceed, analyze and reflect an information through teaching reading always by seeing a text not only for the content, but it also affect students’ behavior to their environment. This is qualitative research with descriptive type. In the beginning of the research, it is done by observing to get the information about students’ problems in implementing critical literacy through reading texts. Besides, researchers will do interview to reading lecturers to know how reading materials had been implemented in Critical Reading class. After that, the reading module was delivered to reading expert to be evaluated and validated. Finally, the teaching reading module in this research can be advantageous for student teachers through teaching reading activity and evaluation to train students to be able to be critically literate.